PENGARUH PENERAPAN SISTEM E-FILLING, PEMAHAMAN PERPAJAKAN, KESADARAN WAJIB PAJAK, SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA KPP PRATAMA DEMAK - Lestari, Utami Puji; Rismawati , Rizky; Ariesta Putri , Marsiska; Aniqotunnafiah (Jurnal Bingkai Ekonomi (JBE), 2024)
This research aims to analyze the effect of implementing the e-filling system, understanding taxation, taxpayer awareness, tax sanctions on individual taxpayer compliance with KPP Pratama Demak. The population in this study is individual taxpayers registered with KPP Pratama Demak. Length of time as an individual taxpayer is more than 2 years. Obtained 125 tax payers. The research sample used the Slovin formula, resulting in 96 people. The sampling technique uses purposive sampling. Data collection techniques use primary data through questionnaires. Data testing uses validity and reliability tests. Data analysis techniques use descriptive statistical analysis, classical assumption UI, multiple linear regression analysis and hypothesis testing. The research results show that understanding taxation, taxpayer awareness, tax sanctions have an influence and the implementation of e-filling has no effect on individual taxpayer compliance at KPP Pratama Demak.